2009
DOI: 10.1017/s1461145709990381
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptophan rescues serotonin response to stress in prefrontal cortex of hyperphenylalaninaemic mice

Abstract: Adult early treated hyperphenylalaninaemic patients can show specific deficits of prefrontal cortical functions. The development of additional therapeutic strategies for these patients requires the understanding of the mechanisms involved in phenylalanine-dependent impairment of fronto-cortical functions. We tested the hypothesis of phenylalanine interference with aminergic neurotransmission in the prefrontal cortex by evaluating, in vivo, amine release in adult Pah(enu2) mice, the genetic model of phenylketon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 55 publications
11
28
0
1
Order By: Relevance
“…It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress. Electrophysiological studies indicated that previous stress and repeated administration of corticotrophin-releasing factor receptor agonist into the BLA reduces GABAergic neurotransmission in this structure, and this impairment is involved in the enhancement of conditioned fear behavior and anxiety (Rodríguez Manzanares et al, 2005;Rainnie et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It was first demonstrated that, in mice, a stressful experience such as restraint induces a time-dependent increase of 5-HT output in the mpFC and of GABA in the BLA, in agreement with previous reports (Reznikov et al, 2009;Pascucci et al, 2009), and that selective depletion of cortical 5-HT canceled out these stress-induced responses, thus pointing to a controlling role of GABAergic transmission in amygdala by prefrontal 5-HT during stress. Electrophysiological studies indicated that previous stress and repeated administration of corticotrophin-releasing factor receptor agonist into the BLA reduces GABAergic neurotransmission in this structure, and this impairment is involved in the enhancement of conditioned fear behavior and anxiety (Rodríguez Manzanares et al, 2005;Rainnie et al, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Artificial CSF was pumped through the dialysis probe at a constant flow rate of 2 ml/min. Experiments were carried out 22-24 h after probe placement as previously described (Pascucci et al, 2009). For reverse microdialysis experiments, TTX (1 mm) was perfused in the BLA for 60 min before restraint stress, and L-allylglycine (1 mM) was perfused in the BLA for 30 min before FST.…”
Section: Microdialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the behavioral phenotype observed in Pah -deficient mice can be partially attributed to lower TPH2 activity in the brain. Interestingly, administration of 5-HTP to Pah -deficient mice restored the cortical release of several monoamines in a model of restraint stress [157] .…”
Section: Tph2mentioning
confidence: 96%
“…Interestingly, it was recently shown that PAH ablation in the mouse causes 70% reduction in 5-HT production in the brain without a loss of the 5-HT precursor tryptophan [156] . Nonetheless, a dramatic reduction in brain 5-HTP levels as well as in the 5-HTP/tryptophan ratio was observed in Pah Enu2-/-mice, suggesting that accumulation of phenylalanine leads to the inhibition of Tph2 activity in vivo, corresponding to its effect on TPH2 activity in vitro [156,157] . Therefore, the behavioral phenotype observed in Pah -deficient mice can be partially attributed to lower TPH2 activity in the brain.…”
Section: Tph2mentioning
confidence: 99%